Nutrient management in paddy fields using remote sensing technique - Teoh, C.C.; Abu Hassan, D.; Muhamad Razali, M.; Jafni, J.J.; Mohd Humaizi, J.; Zamri Khairi, A. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org